Influence of g-phase on the high- temperature oxidation of NiAl-Fe alloys - Monteiro,Maurício de Jesus (1999)
The oxidation of NiAl, NiAl-20at.%Fe and NiAl-30at.%Fe at 1000-1100 °C in air has been studied. Pure NiAl shows excellent oxidation resistance due to the formation of an Al2O3 layer. NiAl-20Fe also shows good oxidation resistance due to the formation of an Al2O3 scale on a b-phase substrate. Moreover, some nodules consisting of mixed oxides of Fe and Ni grow over the ductile g-phase surface incorporated to the b-phase substrate. NiAl-30Fe alloy undergoes a much faster oxidation due to the formation of a non-protective Fe and Ni-rich scale, which is extremely susceptible to spallation. The addition of Fe to NiAl is detrimental to its oxidation resistance.